2019
DOI: 10.2147/opth.s217919
|View full text |Cite
|
Sign up to set email alerts
|

<p>Precision pulse capsulotomy in challenging cataract surgery cases</p>

Abstract: Purpose To evaluate the use of the precision pulse capsulotomy (PPC) device for challenging cataract surgery cases. Patients and methods This single-center retrospective case series study comprised of 43 eyes (from 35 patients) that were challenging cataract surgery cases with poorly dilated pupils, anterior subcapsular opacity, white cataract, brunescent cataract, and corneal opacity. This was  conducted at the Busan Sungmo Eye Hospital (Busan, Republic of Korea) to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The study found that the procedure was useful for complex cases including traumatic cataracts, compromised anterior and posterior capsule, and intumescent cataracts [16]. Similarly, an article evaluating challenging cases exclusively (including poorly dilated pupils, white and brunescent cataracts, and corneal opacity) found that PPC was able to deliver correctly sized free-floating capsulotomies to all eyes ( n = 43) without any anterior capsule tears or tags or postoperative complications [17]. Another study found the same results where PPC was used in triple procedure keratoplasty in patients with small nondilating pupils ( n = 10) [18].…”
Section: Precision Pulse Capsulotomymentioning
confidence: 93%
“…The study found that the procedure was useful for complex cases including traumatic cataracts, compromised anterior and posterior capsule, and intumescent cataracts [16]. Similarly, an article evaluating challenging cases exclusively (including poorly dilated pupils, white and brunescent cataracts, and corneal opacity) found that PPC was able to deliver correctly sized free-floating capsulotomies to all eyes ( n = 43) without any anterior capsule tears or tags or postoperative complications [17]. Another study found the same results where PPC was used in triple procedure keratoplasty in patients with small nondilating pupils ( n = 10) [18].…”
Section: Precision Pulse Capsulotomymentioning
confidence: 93%
“…13 Previous clinical results have demonstrated the efficacy of the device. [14][15][16] As with the femtosecond laser systems, there is some evidence that an automated capsulotomy that does not induce zonular stress may be helpful in complicated cases. 15 The purpose of the current study was to retrospectively review refractive outcomes and complications in a high number of cases completed using the PPC device, comparing them to a similar set of cases completed using a manual CCC technique.…”
Section: Introductionmentioning
confidence: 99%
“…PPC has been used successfully not just in routine cataract surgery but also in pediatric cataract surgery and in challenging cases with corneal opacities, small pupils, zonular pathologies, and trauma. [11][12][13][14][15] The learning curve has been reported to be favorable, and the experience of 4 surgeons has been described. 11 Several device operating principles underlying PPC creation suggest that this technology may also be useful in cases of white cataract.…”
mentioning
confidence: 99%